Forms of Pre-sale (Baye Qabl al-Qabd) in E-commerce - Muhammad Shahid Naeem Khan; Moh-yud-din Hashmi (jihat-ul-islam, 2022)
There are discussed the forms of pre-sale (baye qabl al-qabd) related to e-commerce in this research paper. Exchanging of goods, services and information using the internet is called e commerce. There are various forms of pre-sale (baye qabl al-qabd) in e-commerce, e.g. (1) Selling shares in e-commerce before possession (2) Pre-possession / pre-registry buying and selling of property in e-commerce (3) Pre-sale (baye qabl al-qabd) in forex trading (4) Pre-sale (baye qabl al-qabd) in commodity market (5) Pre-sale (baye qabl al-qabd) in cryptocurrencies, etc. Contemporary scholars have different views on these cases, which give them flexibility and scope. The rules of Islamic Shari’ah about pre-sale (baye qabl al-qabd) will apply. However, due to the change in the custom (Urf) and forms of possession, the rules of Islamic Shari’ah have also changed in many cases. Also, Bayi salam (Advance Sale) and Bayi Istisna’a (sale of pre manufactured) are the best alternatives to pre-sale (baye qabl al-qabd).